Impact of Haulage Transportation on Service Delivery: Evidence from Nigeria - Ogbeide, Augustine Isike (Business and Economic Research, 2024)
This study investigates the impact of haulage transportation on service delivery in Nigeria employing survey evidence from GPC Energy and Logistics Ltd. Haulage transportation was captured by cost of haulage, productivity, and quality. The role of supply chain management (SCM) was measured by customer relationship, degree and quality of information sharing, and services delay. The survey involved a sample population of 310 respondents disaggregated into 110 staff and 200 customers of GPC Energy and Logistics Ltd., using a systematically developed questionnaire in 2022. The locations cut across Abuja, Lagos, Aba, Onitsha and Otta, in Nigeria. The data analysis includes descriptive and inferential statistics of mean ratings and binary logit regression model among others. The mean ratings showed that respondents affirmed that all the indicators of haulage transportation affect service delivery. The respondents also identified turnaround per prime mover and total number of trips per driver as the determinants of service delivery. The estimated logistics model revealed that cost of haulage and productivity of operations increased service delivery potential. It also found that logistics regression increases SCM, implying that customer relationship and degree of information sharing increases the possibility of service delivery. The marginal effects results demonstrated that increase in haulage transportation increases the probability of service delivery. Given these findings, this study recommends among others, that the management of GPC Energy and Logistics Ltd., should prioritize transport management in its haulage operations to increase overall cost efficiency and reduce lead time to create more opportunities for sustainable service delivery in Nigeria.